Biocontrol activities of yeasts or lactic acid bacteria isolated from Robusta coffee against Aspergillus carbonarius growth and ochratoxin A production in vitro - López Rodríguez, Claudia; Strub, Caroline; Fontana, Angélique; Verheecke-Vaessen, Carol; Durand, Noël; Beugré, Corinne; Guehi, Tagro; Medina, Angel; Schorr-Galindo, Sabine (Elsevier, 2024)
Biocontrol Agents (BCAs) can be an eco-friendly alternative to fungicides to reduce the contamination with mycotoxigenic fungi on coffee. In the present study, different strains of bacteria and yeasts were isolated from Ivorian Robusta coffee. Their ability to reduce fungal growth and Ochratoxin A (OTA) production during their confrontation against Aspergillus carbonarius was screened on solid media. Some strains were able to reduce growth and OTA production by 85 % and 90 % and were molecularly identified as two yeasts, Rhodosporidiobolus ruineniae and Meyerozyma caribbica. Subsequent tests on liquid media with A. carbonarius or solely with OTA revealed adhesion of R. ruineniae to the mycelium of A. carbonarius through Scanning Electron Microscopy, and an OTA adsorption efficiency of 50 %. For M. caribbica potential degradation of OTA after 24 h incubation was observed. Both yeasts could be potential BCAs good candidates for Ivorian Robusta coffee protection against A. carbonarius and OTA contamination.
Keywords: A. carbonarius; Aspergillus carbonarius; IARC; International Agency for Research on Cancer; EU; European Union; OTA; Ochratoxin A; ITS; Internal Transcribed Spacer; CCA; Coconut Cream Agar